Relational Heroism of Kartini in Historical Biopic Film Narratives - Zuhdan Aziz; Ariies Budi Marwanto (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This article examines the construction of Kartini's heroism in three Indonesian historical biopics: R.A. Kartini (1982), Surat Cinta untuk Kartini (2016), and Kartini (2017). It departs from the premise that historical films do not merely reproduce the past, but reorganize collective memory through selection, dramatization, and narrative point of view. Using a qualitative interpretive approach, this study applies comparative narrative analysis by combining the Hero's Journey, Todorov's equilibrium structure, and Greimas' actantial model. The data consist of scenes, conflicts, character relations, turning points, and resolutions in the three films. The findings show that Kartini's cinematic heroism does not fully follow an individual monomyth in which a hero leaves home, defeats enemies, and returns with final victory. Instead, the films construct relational heroism: Kartini's agency emerges through networks of family, sisters, correspondence, the people, and feudal-colonial institutions that both constrain and enable her struggle. R.A. Kartini presents Kartini as a national-educative figure, Surat Cinta untuk Kartini mediates her heroism through a romantic male witness, while Kartini emphasizes women's agency and sisterhood. The article concludes that Kartini biopics function as arenas of cultural communication in which history, creative license, gender ideology, and national memory are continuously negotiated.